Desenvolvimento de procedimentos analíticos para a determinação de N-acetilcisteína em produtos farmacêuticos - Suarez, Willian Toito (2005)
In this dissertation four analytical procedures for the determination of Nacetylcysteine in pharmaceutical formulations are described. The first procedure developed was a flow injection analysis system for turbidimetric determination of Nacetylcysteine employing Ag+ ions in an acid medium as the precipitant reagent. In this system, 250 µL of 0.01 mol L-1 AgNO3 solution and 500 µL of sample solution were inserted simultaneously into a merging zones flow system. After the precipitate formation in a 100 cm coil reactor, the precipitate generated was monitored turbidimetrically at 400 nm. Desionised water flowing intermittently at 6.3 mL min-1 was used to wash out the precipitate during the sampling stage. The analytical curve was linear in the N-acetylcysteine concentration range from 1.0 x 10-4 to 1.0 x 10-3 mol L-1; with a detection limit of 8.0 x 10-5 mol L-1 (3σB/slope) and sampling frequency of 60 h-1 was obtained. The relative standard deviation was smaller than 1% for Nacetylcysteine solutions in the concentrations of 1.0 x 10-4 and 5.0 x 10-4 mol L-1 (n=20). The recoveries obtained for two samples ranged from 104 to 122%. A flow injection system with spectrophotometric detection is proposed for determining Nacetylcysteine in pharmaceutical formulations. In this system, N-acetylcysteine was oxidized by Fe(III) and the Fe(II) produced is spectrophotometrically monitored as Fe(II)-1,10-phenantroline complex at 515 nm. Under the optimum analytical conditions, the linearity of the calibration graph for N-acetylcysteine ranged from 1.8 x 10-5 to 1.5 x 10-4 mol L-1. The detection limit of 6.3 x 10-6 mol L-1 (3σB/slope) and recoveries between 102 to 113 % were obtained. The preparation and electrochemical characterization of a carbon paste electrode modified with copper (II) hexacyanoferrate(III) (CuCHF) as well as its behaviour as electrocatalyst toward the oxidation of N-acetylcysteine were investigated. The electrochemical behaviour of the modified electrode and the electrooxidation of N-acetylcysteine were explored using sweep linear voltammetry. The best voltammetric response was observed for a paste composition of 20%(w/w) copper (II) hexacyanoferrate(III) complex, acetate buffer solution at pH of 6.0 as the electrolyte and scan rate of 10 mV s-1. A linear voltammetric response for N-acetylcysteine was obtained in the concentration range xiv from 1.2 x 10-4 to 8.3 x 10-4 mol L-1, with a detection limit of 6.3 x 10-5 mol L-1 (3σB/slope). The proposed electrode is useful for the quality control and routine analysis of N-acetylcysteine in pharmaceutical formulations. Finally, a simple, precise, rapid and low-cast potentiometric method for N-acetylcysteine determination in pure form and in pharmaceutical preparations is proposed. N-acetylcysteine present in tablets containing known quantity of drug was potentiometrically titrated in aqueous solution with AgNO3. No interferences were observed in the presence of common components of the tablets as saccharin, sucrose and EDTA. The analytical results obtained by applying the proposed method compared very favorably with those obtained by the comparative method. Recovery of N-acetylcysteine from various tablets dosage formulations range from 98.7 to 103.0%. Compared to others procedures reported in the literature the procedures developed in this dissertation shows to be better and cheaper to determination of N-acetylcysteine in pharmaceutical formulations.